ETHNIC GROUPS, DEVELOPMENT AND - ' CURRENT SITUATION IN NUNUKAN - John Haba (Research Centre for Population, Indonesian Institute of Sciences, 2006)
In 2002, Nunukan was authoritative as new regency in East Kalimantan. The role of this new regency become more important for its function as a